Correlation between Zinc Intake and Zinc Serum Levels with C-reactive Protein Level in Head and Neck Cancer Patients - Muningtya Philiyanisa Alam; Diana Sunardi; Ikhwan Rinaldi (Indonesian Nutrition Association, 2019)
The inflammatory process of head and neck cancer leads to an increase the proinflammatory cytokines and the synthesis of c-reactive protein (CRP), which then causes metabolic alteration and anorexia in the patients. Zinc is one of nutrient that has an important role in suppressing inflammation, but it is reported that about 65% of head and neck cancer patients have zinc deficiency. The aim of this cross sectional study is to determine the correlation between zinc intake and serum zinc levels with CRP level as an effort in reducing inflammation process in head and neck cancer patients. Subjects were collected by consecutive sampling in the Oncology Polyclinic Rumah Sakit Kanker Dharmais, from 49 subjects 67,3% were men, most subjects were in the age range between 46–65 years. The highest frequency (65,3%) is nasopharyngeal cancer and 69,4% are already in stage IV. All subjects (100%) in this study have a zinc intake below the recommended dietary allowance (RDA) in Indonesia. The mean serum zinc level of the subjects was 9.83±2.62 μmol/L. Most subjects have elevated CRP levels. There was a weak negative correlation between zinc concentration and CRP levels of subjects (r =-0.292, p =0.042), but there was no correlation between zinc intake and CRP levels of subjects (r =-0.25).